Analisis Peran Guru dalam Pengelolaan Kelas pada Pembelajaran Tematik Kelas V di SDN Karanganyar 3 Kota Tangerang - Roro Rachmi Dewanti; Yeni Nuraeni; Septy Nurfadhillah (AS-SABIQUN, 2022)
This study aims to find out and describe the main activities and strategies carried out by a teacher to minimize problems in classroom management in class V thematic learning at SDN Karanganyar 3 Tangerang City. This study uses descriptive qualitative methods, namely methods that involve researchers directly to observe the object being studied. The results of the research obtained by the researcher are the main activities in SDN Karanganyar 3 Tangerang City, the lack of a teacher in organizing students in the classroom and the lack of material supporting the material that is very little. in this case, the teacher must be able to make agreements with students in managing the class and students cannot understand the material because of the lack of supporting materials from thematic guidebooks at school. This means that the teacher must always be alert in handling the class properly and make the learning atmosphere in the class interesting so that students do not get bored in learning.